Control de la roya blanca (Puccinia horiana Henn.) en crisantemo (Dendranthema grandiflora Tzvelev.) variedad Spider - Corona Rodríguez, María del Carmen; García Frías, Armando; Norman Mondragón, Tomás H.; Aquino Martínez, Jesús G.; Sandoval Rosales, Fernando R.; Vázquez García, Luis Miguel (CIENCIA ergo-sum; Vol. 4 Núm. 2 (1997): CIENCIA ergo-sum (julio-octubre 1997), 2017)
-